A Study on Human Impulses Towards Civilization As Described In William Golding’S Novel ‘Lord of the Flies’: Exploring the Influence of Human Impulses on Civilization (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Published in 1954, Lord of the Flies was Golding’sfirst novel. Although it was not a great success at the time- selling fewerthan 3,000 copies in the United States during 1955 before going out of print-it soon went on to become a best-seller, and by the early 1960s was requiredreading in many schools and colleges. It has been adapted to film twice inEnglish, in 1963 by Peter Brook and 1990 by Harry Hook, and once inFilipino (1976).